Transforming historical to personal nostalgia: A God’s way in empowering Joshua’s leadership - Surbakti, Pelita H.; Andangsari, Esther W. (Verbum et ecclesia, 2025)
One of the most prominent themes in the Book of Joshua is leadership. However, the process through which God moulded Joshua and the role Joshua played in ultimately becoming a remarkably resilient leader is hardly discussed. In our opinion, nostalgia about God is the key to Joshua’s resilience. Although nostalgia, functioning as an inner resource that fosters hope within individuals, has been extensively studied and empirically validated in psychology, its role in shaping and portraying the factors contributing to the resilience of a new leader, as depicted in the Book of Joshua, has remained largely unexplored. Intriguingly, the nostalgia about God is an inclusive framework that encapsulates the entire book (Jos 1:2–5 and 24:25–27). To further reinforce Joshua, the narrative is replete with instances where God transforms historical nostalgia about Himself into personal nostalgia. This personal nostalgia empowers Joshua to lead with unwavering strength.Intradisciplinary and/or interdisciplinary implicationsDrawing on the psychological concept of nostalgia, this article examines how God empowered Joshua as a new leader. Thus, theoretically, this article proposes a new perspective for reading the Book of Joshua. Still, practically, it can also serve as a model for anyone who wants to shape strong individuals or leaders in the future.